Analysis of Intracranial Meningioma Recurrence after Surgical Management - Nashwan Nashat Mawlood Al-saffar ,; Imad Khaleel Hammood (Diyala Journal of Medicine, 2022)
Background: Meningioma is one of the well-known common primary brain neoplasms that account for more than 20% of intracranial tumors. Intracranial meningioma recurrence after surgery has long been recognized, although the mechanism of recurrence remains unclear.